Seasonal variation in types of stroke and its common risk factors - Miah, AH; Sutradhar, SR; Ahmed, S; Bhattacharjee, M; Alam, MK; Bari, MA; Tariquzzaman, M; Mondol, GD; Khan, NA; Sarker, CB (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):13-20 The abstract of this article is available on the PubMed website